Gerobox Santai Online Ordering System - anwar, nurin; Omar, Nurul Aswa (Applied Information Technology And Computer Science, 2024)
The Gerobox Santai Online Ordering System is a system that was developed to help the restaurant manage and keep track of takeaway orders. As Gerobox Santai has been established since the year 2018, Gerobox Santai is able to promote and provide their services to customers who prefer to have their meal delivered. Usually, customers are asked to order manually at the restaurant, which is time-consuming for the customer who would like to have a takeaway order. Besides, it will lead to the inefficiency of the restaurant service as the orders cannot be organised well due to the lack of a systematic and orderly system. The objective of the project is to be able to develop an online ordering system that focuses on takeout for Gerobox Santai customers. The Gerobox Santai system is built for three types of users: customers, riders, and staff, with the owner of the restaurant as the administrator. For the customers and the rider, the system will be accessible from a smartphone, while a web-based application can be accessed by the administrators. The methodology used is the waterfall model, which allows the task distribution to be divided into requirement analysis, design, implementation, and testing phases. The Android Studio Code software will be used to develop the mobile application, while the Visual Studio Code software will be used in the development of the web application. Thus, the data will be stored in the Firebase real-time database.